[6] Overactive bladder amongst Saudi women: Its prevalence, risk factors, and effect on quality of life - Riyad Al Mousa (Taylor & Francis Group, 2018)
Objective: To assess the prevalence and risk factors of overactive bladder syndrome (OAB), and its impact on quality of life (QoL) in Saudi women. Methods: A cross-sectional, observational epidemiological study was carried out in women aged ⩾18 years to define the prevalence of OAB, risk factors, and the effect on QoL, by self-completed OAB-Short Form (OAB-SF) questionnaire over the period of February to March 2018 in the Eastern province of Saudi Arabia. The OAB-SF questionnaire was translated into Arabic and some questions were developed by the researchers. The questionnaire includes: age, sex, parity, body mass index, education, urinary tract infection (UTI), smoking, chronic medical illness [diabetes mellitus (DM), hypertension, neurological diseases], and menopause. Questions covered:1. Storage symptoms (urgency, nocturia, frequency, and urge urinary incontinence [UUI]).2. Severity of symptoms and their effect on QoL. Results: Data were analysed from 566 responders through either electronic or paper forms. Most responding women were non-smokers (86%), college-graduated (77%), and of childbearing age (87%), with regular menstruation (84%). Obesity prevalence was 63%. Frequent UTIs and other comorbidities (DM, hypertension and neurological disorders) were uncommon, at 18% and 12%, respectively. The prevalence of storage symptoms was common (urgency 62%, frequency 74%, nocturia 75%, and UUI 43%). These OAB storage symptoms were associated with negative effects on QoL; 66% of the respondents had to wake at night and/or look for a restroom in public places to urinate. Using an ordinal regression model to study risk factors associations with either urgency or nocturia; only number of children was statistically significant as an independent variable (P < 0.05). Both age and weight were not significant. Conclusion: OAB is highly prevalent amongst Saudi women with negative effects on QoL. The number of children was a significant risk factor for either urgency or nocturia. Comprehensive healthcare programmes are needed for the diagnosis and management of this syndrome.